Textual Analysis of the Baode Oral Tradition of Banggai Community in South Buko: An Anthropolinguistic Study - Rahmi Ningsi Yadalia; Indah Apriani Tayudi; Srilidiawati Epa; Nurlaela (Kawruh: Journal of Language Education, Literature and Local Culture, 2026)
This study analyzes the Baode oral tradition of the Banggai community in Lumbi-lumbia Village, South Buko District, Central Sulawesi, through the perspectives of anthropolinguistics macrostructure, superstructure, and microstructure. Employing a descriptive qualitative method with interviews, observations, and recordings as data collection techniques, the research draws on anthropolinguistics as the theoretical framework. The findings show that at the macrostructure level, the Baode text highlights themes of respect for ancestors, the preservation of customs, and the transmission of moral values across generations. The superstructure is organized into a coherent sequence of opening, body, and closing, designed to facilitate audience comprehension and to emphasize the moral messages of the performance. At the microstructure level, lexical and connotative analyses reveal the use of local vocabulary, metaphors, and repetition as expressions of politeness, cultural identity, and resistance to modernization. Overall, the study demonstrates that Baode is more than a form of entertainment: it represents the local wisdom of the Banggai people, functioning as a medium of cultural preservation, identity reinforcement, and social solidarity that requires revitalization in the face of globalization and declining intergenerational transmission.